KEPENTINGAN RUSIA MENINGKATKAN PENJUALAN SENJATA KEPADA REZIM BASHAR AL-ASSAD DALAM KONFLIK SURIAH TAHUN 2011-2013 - Abdi, Zainal; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research to explain the reasons of Russia supplies weapon to bashar al-assad in Syria conflict. Syria is one of the countries in Middle East that is experiencing political turmoil with people demanding President Bashar al-Assad retreated from his position. This conflict has claimed of so many people life that western countries lead to implement the arms and other economic sanctions against Syria but the effort was opposed by Russia through its veto.The foreign policy theory tries to explain the decision of Russia as a form of maintaining power in Middle East, particularly in Syria. in addition, rusia Russia has an interest in Syria. The scope of this study is from 2011-2013.Keywords: Foreign Policy, National Interest, Conflict, trade of weapon